Healthy work. Challenges and opportunities to 2030 - Vaughan-Jones, Helen; Barham, Leela (London, 2009)
"Unless addressed, the worsening health of the workforce will damage the long-term productivity of British companies large and small. By 2030, an ageing workforce and higher rates of chronic disease among employees will pose a serious threat to business success. This report, led by Bupa, the health and care company, and published in partnership with The Work Foundation, The Oxford Health Alliance and RAND Europe, brings together for the first time more than 200 pieces of research to provide in-depth insight into how the health of British workers will change over the next 20 years. It argues that work – and in particular good work – must be placed at the centre of efforts to improve health."